Exploring the Role and Benefits of ChatGPT AI in Enhancing Students' Fiction Writing Literacy: Insights from Learner Experiences - Kholilah Yuniar Nasution; Rani Amelia Sihite; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores the perspectives of literature students on utilizing ChatGPT, an AI-powered tool, in creative writing. Focusing on 30 English literature students from Universitas Negeri Medan, the research examines the effectiveness of ChatGPT in fostering creativity, its perceived benefits and challenges, and its role in the writing process. Data were collected via questionnaires and analyzed thematically. The findings reveal that ChatGPT significantly enhances creativity, with students rating it highly for its ability to inspire ideas and improve the writing process. The tool was praised for accelerating the writing process and improving writing confidence. However, challenges such as the need for revisions and limitations in contextual understanding were also noted. Despite these drawbacks, the overall sentiment remained positive, with many participants feeling that the benefits of using ChatGPT outweighed its limitations. This study underscores ChatGPT’s potential as a valuable tool in literary education, supporting students' creative autonomy and enriching their writing experiences. This is evidenced by data highlighting the effectiveness of ChatGPT in speeding up the writing process (60%), increasing creativity (46.67%), and increasing confidence in writing (40%), despite challenges such as unmet expectations (46.67%) and requires a lot for revision (33.33%).